Casual Games Before Casual Games: Historicizing Paper Puzzle Games in an Era of Digital Play. Issue 2 (March 2019) - Johnson, Mark R.
This article examines "paper puzzle games"—crosswords, Sudoku, Kakuro, word searches, and so forth—in order to historicize and contextualize "casual games, " complicate our notions of "casual" play, and open up paper puzzle games to game studies consideration for the first time. The article begins by identifying the dearth of literature on paper puzzle games and offers an initial examination of these games through the lens of casual games, play, and players. It focuses on six traits in casual game design: appealing themes, ease of access, ease of learning, minimal required expertise, fast rewards, and temporal flexibility. It demonstrates that—from a perspective of mechanics, demographics, and contexts of play—paper puzzle games are excellent examples of casual games and therefore important to fully study. It also shows the complexity of paper puzzles as a topic in their own right, opening them up for future examination.